Insect vectors of banana blood disease in Flores Island, East Nusa Tenggara, Indonesia - MAYAVIRA V. HAHULY; I WAYAN MUDITA; AGNES V. SIMAMORA; PETRONELLA S. NENOTEK; SRI WIDINUGRAHENI; VIKTORIANUS JEHAUT; FADLAN PRAMATANA (Society for Indonesian Biodiversity, 2025)
Abstract. Hahuly MV, Mudita IW, Simamora AV, Nenotek PS, Widinugraheni S, Jehaut V, Pramatana F. 2025. Insect vectors of banana blood disease in Flores Island, East Nusa Tenggara, Indonesia. Biodiversitas 26: 3791-3802. Banana Blood Disease (BBD) poses a significant threat to banana cultivation in Indonesia. Following severe outbreaks on Sumba Island, the disease spread to the neighboring Flores Island in mid-2022, with a particularly pronounced impact on the predominant cultivar, Musa sp. ABB ‘Kepok plantain.’ Despite prior outbreaks, awareness and understanding of the disease and its insect vectors remain limited among agricultural officers, village leaders, and farmers on Flores Island. The pathogen, Ralstonia syzygii subsp. celebesensis (Rsc), is known to be transmitted by insect vectors; however, no prior data existed regarding vectors on Flores Island. This knowledge gap has impeded effective disease management and allowed the disease to spread unnoticed. This study aimed to assess the spread and incidence of BBD and investigate potential insect vectors involved in its transmission. A survey conducted across five districts in western Flores confirmed the presence of BBD in all surveyed areas, with varying incidence rates among banana cultivars. The highest incidence (65.88%) was recorded in Musa sp. ABB ‘Kepok plantain,’ followed by Musa sp. AAB ‘Raja Sereh banana,’ Musa sp. AAA ‘Barangan banana,’ Musa sp. AAA ‘Cavendish banana,’ and Musa sp. BB ‘Klutuk plantain.’ Insect surveys identified eight species visiting male banana inflorescences. Among them, Oscinella sp. (Diptera: Chloropidae) and Bactrocera sp. (Diptera: Tephritidae) were the most widespread and abundant. These species have previously been reported as BBD vectors in other regions. They were likely key contributors to the spread of Rsc on Flores Island.